Enhancement of field electron emission in topological insulator Bi2Se3 by Ni doping. Issue 27 (27th June 2018) - Mazumder, Kushal; Sharma, Alfa; Kumar, Yogendra; Bankar, Prashant; More, Mahendra A.; Devan, Rupesh; Shirage, Parasharam M.
Abstract : Nanostructures of bismuth selenide (Bi2 Se3 ), a 3D topological insulator material, and nickel (Ni) doped Bi2 Se3 samples were prepared by a hydrothermal method to explore the field emission properties. Abstract : Nanostructures of bismuth selenide (Bi2 Se3 ), a 3D topological insulator material, and nickel (Ni) doped Bi2 Se3 samples were prepared by a hydrothermal method to explore the field emission properties. An enrichment in the field electron emission (FE) properties in terms of the threshold and turn-on field values of Bi2 Se3 and Ni doped Bi2 Se3 nanostructures was measured at a base pressure of ∼1 × 10 −8 mbar. Using the background of the Fowler–Nordheim (FN) theory a field enhancement factor ( β ) of 5.7 × 10 3 and a threshold field value of 2.5 V μm −1 for 7.5% Ni doped Bi2 Se3 were determined by investigating the J – E plot of the FE data. The value of β is three times higher than that of pure Bi2 Se3 confirming the superior FE properties. The emission current was found to be very stable with the property of long standing durability as a negligible amount of variation was observed when measured at a constant value of 5 mA for 3 hours. The experimental results signify many opportunities for potential applications of Ni doped Bi2 Se3 as a source of electrons in scanning as well as transmission electron microscopy, flat panel displays and as an X-ray generator, etc.